Risk factors of early recurrence after curative hepatectomy in hepatocellular carcinoma. Issue 10 (October 2017) - Hong, Young Mi; Cho, Mong; Yoon, Ki Tae; Chu, Chong Woo; Yang, Kwang Ho; Park, Yong Mok; Rhu, Je Ho
Early recurrence is common after curative hepatectomy for hepatocellular carcinoma and is associated with poor prognosis. This study aimed to identify risk factors of early recurrence after curative hepatectomy in hepatocellular carcinoma. Overall, 63 patients who underwent curative hepatectomy for hepatocellular carcinoma were enrolled. Patients were divided into the early recurrence group, who developed recurrence within 12 months after hepatectomy (n = 10), and the non-early recurrence group (n = 53). Clinicopathological factors of early recurrence were retrospectively analyzed. Among the 63 patients, 10 (15.9%) patients experienced early recurrence. Univariate analysis showed tumor necrosis (p = 0.012), level of PIVKA-II (prothrombin induced by vitamin K absence or antagonist-II; p = 0.002), and microvascular invasion (p = 0.029) to be associated with early recurrence. By multivariate analysis, there were significant differences in high PIVKA-II (p < 0.001) and tumor necrosis (p = 0.012) in patients with early recurrence. The optimal cutoff values of PIVKA-II and tumor necrosis were 46 mAU/mL and 3% of total tumor volume, respectively. Patients with a high preoperative PIVKA-II level and extent of tumor necrosis, which are independent risk factors for early recurrence, should be actively treated and monitored closely after hepatectomy.